Access and engagement in HIV care among a national cohort of women living with HIV in Canada. Issue 10 (3rd October 2017) - Kronfli, Nadine; Lacombe-Duncan, Ashley; Wang, Ying; de Pokomandy, Alexandra; Kaida, Angela; Logie, Carmen; Conway, Tracey; Kennedy, V. Logan; Burchell, Ann; Tharao, Wangari; Pick, Neora; Kestler, Mary; et al.
ABSTRACT: Attrition along the cascade of HIV care poses significant barriers to attaining the UNAIDS targets of 90-90-90 and achieving optimal treatment outcomes for people living with HIV. Understanding the correlates of attrition is critical and particularly for women living with HIV (WLWH) as gender disparities along the cascade have been found. We measured the proportion of the 1425 WLWH enrolled in the Canadian HIV Women's Sexual and Reproductive Health Cohort Study (CHIWOS) who had never accessed HIV medical care, who reported delayed linkage into HIV care (>3 months between diagnosis and initial care linkage), and who were not engaged in HIV care at interview (<1 visit in prior year). Correlates of these cascade indicators were determined using univariate and multivariable logistic regression. We found that 2.8% of women had never accessed HIV care. Of women who had accessed HIV care, 28.7% reported delayed linkage and 3.7% were not engaged in HIV care. Indigenous women had higher adjusted odds of both a lack of access and delayed access to HIV care. Also, a younger age, unstable housing, history of recreational drug use, and experiences of everyday racism emerged as important barriers to ever accessing care. Programmatic efforts to support early linkage to and engagement in care for WLWH in Canada must address several social determinants of health, such as housing insecurity and social exclusion, and prioritize engagement of Indigenous women through culturally safe and competent practices.